A REVIEW OF A FINTECH FINANCING PLATFORM: POTENTIAL AND CHALLENGES OF ISLAMIC CROWDFUNDING TO ENTREPRENEURS (International Journal of Islamic Business, 2023)
The emergence of financial technology, known as fintech, has altered the landscape of traditional financial institutions. Broadly defined, fintech is the application of technology in finance. Conventional and Islamic crowdfunding platforms are fintech innovations that offer a great alternative to traditional financial lenders like banks. This paper aims to provide insights regarding crowdfunding as an alternative fundraising source for entrepreneurs, especially start-ups, who usually face financial challenges. This paper uses a deskresearch methodology to review the extant literature on crowdfunding as an entrepreneur's funding source. Findings show that crowdfunding adoption is rapidly increasing and is embraced by many underserved entrepreneurs. As a promising alternative, it offers excellent potential by providing services at a lower transaction cost and greater efficiency. It also covers a broader market penetration. Islamic crowdfunding benefits even more, as the nature of Islamic financing helps to curb excessive credit expansion, thus helpingto stabilise the economy. The application and importance of Islamic crowdfunding are in line with the three classes of Maqasid-Shariah, which are darūrāt (necessities), ḥājīyāt (needs), and taḥsīnīyāt (luxuries). Nevertheless, crowdfunding is not without problems and challenges. Major problems usually arise from regulatory and fraud issues, such as stolen ideas and lack of proper regulations. This paper may help create awareness about crowdfunding, its potential, and its challenges to entrepreneurs. The findings may alsoserve as reference points for future researchers to examine further the issues and challenges in the crowdfunding industry, especially Islamic crowdfunding, in promoting competency and sustainability for entrepreneurs' interests.